Production Efficiency Measurement of Seaweed Cultivation In The Specific Economic Zone of Mandalika, Central Lombok Regency - Muhammad Nursan; Syarif Husni; M. Yusuf; Aeko Fria Utama FR; Ni Made Nike Zeamita Widiyanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Central Lombok Regency, especially in the Specific Economic Zone (SEZ) Mandalika apart from being a tourism area it is also one of the centers for seaweed cultivation in NTB Province, seaweed cultivation in the SEZ Mandalika, Central Lombok Regency currently still has several problems, one of which is business productivity which is still low. The low productivity of seaweed cultivation can be caused by inefficient allocation of inputs. The aims of this study were: 1) to analyze the factors that affect the production of seaweed aquaculture, 2) to analyze the level of efficiency of the production of seaweed aquaculture, and 3) to analyze the factors that influence the level of technical inefficiency of seaweed cultivation in SEZ Mandalika, Central Lombok Regency. This study uses a descriptive research method with a mixed method research approach. Collecting research data using survey techniques through interviews with respondents as many as 30 people who were taken by accidental sampling. Analysis of the data in this study using the method of Cobb-Douglas stochastic frontier production function to measure the level of production efficiency of seaweed cultivation in SEZ Mandalika, Central Lombok Regency. The results of this study indicate that seaweed production is significantly influenced by the variables of area, seeds, and labour. The level of production efficiency of seaweed cultivation is efficient with a production efficiency value of 0.861. Then the factors that affect the technical inefficiency of seaweed cultivation in Central Lombok Regency include level of education and dummy farmer groups.